MEDIA WEBSITE EDUKASI INTERAKTIF UNTUK PENCEGAHAN DIABETES MELITUS TIPE 2 DI SMAN 4 CIMAHI - Dhiya, Alfiya Salma; Karjatin, Atin (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Indonesia faces health challenges, especially with the increasing prevalence of non-communicable diseases (NCDs) such as Type 2 Diabetes Mellitus (DM), particularly among adolescents. The National Diabetes Statistics Report (2017) reported a DM prevalence of 7.2% among children and adolescents in 2015, while data from the Cimahi Health Department (2023) showed a 20% increase in DM cases among adolescents over the past two years. Objective: To assess the feasibility of an interactive educational website for Type 2 diabetes prevention at SMAN 4 Cimahi using the 4D approach (Define, Design, Development, Dissemination). Methods: This study used the 4D approach, involving define, design, development with material testing, media testing, small-scale trials, and statistical analysis using a quasi-experimental one-group pretest-posttest design, with a sample of 81 respondents and dissemination Results: Analysis revealed that students required an interactive educational website on Type 2 diabetes. The website was designed with menu navigation features, relevant images, and compatibility for both smartphones and laptops, with a blue color theme and sans-serif font. The statistical tests indicated the media was highly feasible and had a significant impact on adolescents' knowledge for Type 2 diabetes prevention. The media can be accessed via the provided link. Conclusion: The interactive educational website for Type 2 Diabetes Mellitus is highly feasible and accessible via the link (https://instingku-e718a.website.app/).